Sustainable Business Practices in Industrial Sector: The Perspective of Debt Diversification, Corporate Social Responsibility, Firm Size, and Firm Value - Sari , Dyan Risetya Rafiqa; Vina Febriana; Marsintauli, Frihardina (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
The company’s current vision is centered on its goals and objectives. Its sustainability is no longer limited to gaining profit alone; it also includes external aspects that impact the company. Based on the Triple Bottom Line concept, which integrates how companies balance profit, people, and environmental interests in carrying out their business activities. This study aims to analyze the effects of debt diversification, corporate social responsibility, and company size on the value of industrial sector companies listed on the IDX from 2020 to 2022. The novelty of this research lies in its adjustment of the debt diversification measurement by the Financial Accounting Standards in Indonesia (PSAK). The sampling technique used was purposive sampling, combined with quantitative research, to test 42 companies. SPSS 23 software was used to produce panel data regression. The study showed that debt diversification affected company value, while Corporate Social Responsibility and company size did not. It shows that the industrial sector still tends to focus on the company’s internal strengths, which include increasing profits because it believes that the company’s desires are formed from its economic strength compared to environmental and social aspects.